Sub-dimensions of Alcohol Use Disorder in Alcohol Preferring and Non-preferring Rats, a Comparative Study - Domi, Ana; Stopponi, Serena; Domi, Esi; Ciccocioppo, Roberto; Cannella, Nazzareno (Frontiers in Behavioral Neuroscience, 2019)
Current animal models of alcoholism provide limited conclusions about individual differences in dependence vulnerability. Here, we used genetically selected Marchigian Sardinian alcohol-preferring (msP) and Wistars rats to apply a multidimensional model of alcohol use disorder (AUD) adapted from a previously described DSM-IV/DSM-5 multisymptomatic cocaine addiction model. As proof of concept, we hypothesized that msP rats, genetically selected for excessive drinking, would be more prone to develop dependence-like behavior compared to Wistars. Before exposure of animals to alcohol, we monitored basal anxiety in the elevated plus maze (EPM). Animals were then trained in prolonged operant alcohol self-administration, consisting of 30 minute daily sessions for 60 days in total. Each session consisted of two 10-minute periods of alcohol reinforcement separated by 10-minute interval of non-reinforcement. Following training, we applied three criteria of individual vulnerability for AUD: 1) Persistence of lever pressing for alcohol when it was not available; 2) Motivation for alcohol in a progressive ratio schedule of reinforcement; 3) Resistance to punishment when alcohol delivery was anticipated by a foot-shock (0.3 mA). We obtained four groups corresponding to the number of criteria met (0-3 crit). Rats in the 0crit and 1crit groups were characterized as resilient, whereas rats in the 2crit and 3crit groups were characterized as prone to develop a dependent-like phenotype. As predicted, the 2-3crit groups were enriched with msP rats while the 0-1crit groups were enriched in Wistar rats. In further analysis we calculated the global addiction score (GAS) per subject by the sum of the normalized score (z-score) of each criteria. Results showed GAS was highly correlated with animal distribution within the 3 criteria. Specifically, GAS was negative in the 0-1crit groups, and positive in the 2-3crit groups. A positive correlation between basal anxiety and quantity of alcohol intake was detected in msP rats but not Wistars. In conclusion, we demonstrated that the 0/3criteria model is a suitable approach to study individual differences in AUD and that msP rats, selected for excessive-alcohol drinking, show a higher propensity to develop AUD compared to non-preferring Wistars.